Additive manufacturing of AlSi10Mg samples using the selective laser melting technique: correlation between tensile and torsion behaviour. Issue 7 (20th July 2020) - Sert, E.; Hitzler, L.; Merkel, M.; Werner, E.; Öchsner, A.
Abstract: Additive manufacturing offers unique possibilities to produce complex components, which would not be possible or only very difficult to be realizable with conventional manufacturing processes. The potential of additive manufacturing of aluminum alloys has already been realized in prototyping, but still offers potential in the establishment of series applications. For enabling the establishment of additive manufacturing in series applications, comprehensive knowledge about the material behavior is necessary. This study examines the torsional behavior of additive manufactured AlSi10Mg samples and shows the correlation between tensile and torsional strength. Comprehensive torsion tests with strain gauges were performed and significant directional dependencies were shown. The correlation factor in the area of torsional yield strength/tensile yield strength and torsional strength/tensile strength was determined and was compared with the yield/failure conditions according to Tresca and von Mises. Abstract : In the context of elasto‐plastic material modelling, the yield condition is an important constituent of the plastic material law. Whether these classical laws are potentially applicable to additively manufactured materials is investigated in this study on the correlation between tensile and torsional strength. Translation abstract: Die additive Fertigung bietet einzigartige Möglichkeiten komplexe Bauteile herzustellen, die mit konventionellen Fertigungsverfahren nicht oder nur sehr schwer, realisierbar wären. Das Potenzial der additiven Fertigung von Aluminiumlegierungen ist heute im Prototyping bereits erkannt, birgt aber noch Potenzial in der Etablierung der Serienapplikation. Um die Etablierung der additiven Fertigung in den Serienapplikationen zu ermöglichen, sind umfangreiche Erkenntnisse über das Materialverhalten notwendig. Diese Studie befasst sich mit dem Torsionsverhalten additiv gefertigter AlSi10Mg Proben und stellt zudem die Korrelation zwischen Zug‐ und Torsionseigenschaften dar. Umfangreiche Torsionsversuche mit Dehnungsmessstreifen (DMS) wurden durchgeführt und signifikante Richtungsabhängigkeiten wurden aufgezeigt. Der Korrelationsfaktor im Bereich Torsionsfließgrenze/Streckgrenze und Torsionsfestigkeit/Zugfestigkeit wurde ermittelt und mit den Fließbedingungen nach Tresca und von Mises verglichen.